Determinants of the Trade Balance in India. Evidence From a Post-liberalisation Period - Parray, Waseem A.; Wani, Suadat H.; Yasmin, Effat (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2022)
The present study investigates trade balance determinants in post-liberalization India from 1991 to 2020. The main aim of this study is to test the validity of the J-curve and Marshal-Lerner condition and examine the impact of other related macroeconomic variables, including foreign income, exchange rate, domestic prices, and domestic demand on the country’s trade balance. To achieve this objective, bounds tests and error correction model within asymmetric and symmetrical framework was used for estimation. In addition, variance decomposition analysis was applied to examine the dynamic interaction of selected variables. The results indicate the absence of the ’J-curve’ effect and ’Marshall-Lerner’ condition in India. Further, the results indicate that domestic prices, domestic demand, and money supply have negative signs, whereas exchange rate and world demand have positive signs in the long and short-run. The results from the variance decomposition indicate that as compared to other variables, the exchange rate highly contributes to forecasting error variance of trade balance in the case of India.